CREATING A DATABASE OF UZBEK PROVERBS: THEORETICAL AND METHODOLOGICAL FOUNDATIONS - Ruziev Khusniddin Bakhritdinovich, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Proverbs are an important part of a nation's linguistic and cultural heritage, reflecting collective wisdom, social values, and historical experience. Recent advances in corpus linguistics and digital technologies have transformed traditional approaches to proverb research, enabling the systematic collection and analysis of large-scale paremiological data. This study explores the theoretical and methodological foundations of creating a database of Uzbek proverbs, focusing on data collection, corpus design, metadata organization, and annotation procedures. The paper argues that a structured electronic proverb database can serve as an effective resource for corpus-based paremiological, linguocultural, and translation studies, while also supporting the development of multilingual proverb corpora.
Keywords: Keywords: Uzbek proverbs, proverb database, corpus linguistics, paremiology, annotation, linguocultural studies.